Construction of a consistent YAC contig for human chromosome region 3p14.1. - Bardenheuer, W; Michaelis, S; Lux, A; Vieten, L; Bröcker, F; Jülicher, K; Willers, C; Siebert, R; Smith, D I; van der Hout, A H; Buys, C; Schütte, J; et al.

(untitled) (Genome Research, 1996)
Chromosomal deletions and translocations of human chromosome region 3p14 are observed in various human malignancies and suggest the existence of a tumor suppressor gene locus within this region. Tumors most frequently affected by these aberrations are small-cell lung cancer and renal-cell carcinoma. In continuation of our previously published YAC contig of chromosome region 3p14.2-p14.3, we report here on the construction of a YAC contig of at least 11 Mb that consisted of 171 YACs and covers the entire subregion 3p14.1. This contig includes the t(3;8) breakpoint of a hereditary renal-cell carcinoma localized in 3p14.2 and extends into human chromosome region 3p12-p13. It defines the order of 34 DNA probes in relation to reference markers D3S6 and D3S30 as well as the human protein tyrosine phosphatase-gamma gene. For 31 DNA probes we identified nonchimeric YACs by fluorescence in situ hybridization. The minimal tilling pathway consists of 16 yeast artificial chromosomes. As a prerequisite for identification of a putative tumor suppressor gene within this region, this contig renders human chromosome region 3p14.1 accessible to gene isolation.